A study on the impact of capitalization on the profitability of banks in emerging markets: A case of Pakistan - Muhammad Haris; Yong Tan; Ali Malik; Qurat Ul Ain (Journal of Risk and Financial Management, 2020)
A strong capitalized position of financial institutions is essential to ensure their solvency. Because of their unique nature, banks must always keep an optimum level of capital to ensure smooth banking earnings. Consequently, it is mandatory for all types of banks operating in Pakistan to keep a minimum amount of required capital along with capital adequacy to remain solvent and profitable. Therefore, using three measures of capitalization, i.e., the Capital Ratio (CR), Capital Adequacy Ratio (CAR), and Minimum Capital Requirement (MCR), and four measures of profitability, i.e., Return on Avg. Assets (ROAA), Return on Avg. Equity (ROAE), Net Interest Margin (NIMAR), and Profit Margin (NMAR), this study contributes to the existing literature on the relationship between the capitalization and profitability of 29 Pakistani banks over the period of 2007-2018. The results, based on the Generalized Method of Moments (GMM) system estimator technique, reported an inverted U-shaped relationship between the two capitalization measures, i.e., CR and CAR, and the four profitability measures, i.e., ROAA, ROAE, NIMAR, and NMAR. This indicates that profitability increases with an increase in capitalization up to a certain level, while beyond that level, a further increase in capitalization decreases profitability. The results also indicate that banks who maintain their MCR have higher profitability than those who do not.
Keywords: 330; bank profitability; capital adequacy ratio; capital ratio; minimum capital requirement